2009
DOI: 10.1111/j.1470-6431.2009.00748.x
|View full text |Cite
|
Sign up to set email alerts
|

Consumer concern, knowledge and attitude towards counterfeit apparel products

Abstract: The purpose of this paper was to explore the relationship of three variables (concern with apparel industry issues, knowledge about counterfeiting and attitude towards counterfeit apparel products) with consumer willingness towards paying a premium for non‐counterfeit goods. The intent of the research was to develop a theoretically based foundation from which educators and apparel industry leaders can develop policy regarding counterfeit goods. Will consumer concern and knowledge influence the behavioural inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(68 citation statements)
references
References 31 publications
2
64
0
2
Order By: Relevance
“…The influence of consumer knowledge on their acceptance of service brands and adoption of new technology and innovation has long been established in the marketing and consumer behaviour literature. Thus, the findings confirm numerous studies (e.g., Rogers, 1962Rogers, , 2003Rogers, 2003;Cordell, 1997;Huang, Hsieh, & Chang 2011;Marcketti & Shelley, 2009) that consumers' knowledge plays a key and leading www.ccsenet.org/ijms International Journal of Marketing Studies Vol. 6, No.…”
Section: Discussion Of Findings and Implications To Theorysupporting
confidence: 78%
See 1 more Smart Citation
“…The influence of consumer knowledge on their acceptance of service brands and adoption of new technology and innovation has long been established in the marketing and consumer behaviour literature. Thus, the findings confirm numerous studies (e.g., Rogers, 1962Rogers, , 2003Rogers, 2003;Cordell, 1997;Huang, Hsieh, & Chang 2011;Marcketti & Shelley, 2009) that consumers' knowledge plays a key and leading www.ccsenet.org/ijms International Journal of Marketing Studies Vol. 6, No.…”
Section: Discussion Of Findings and Implications To Theorysupporting
confidence: 78%
“…Cordell (1997) empirically found that consumers' knowledge of the existing product or service category is a leading factor that affects the adoption process. Similarly Marcketti and Shelley (2009) maintained that consumers' knowledge of products has a significantly positive effect on their adopting intentions. More recently, Huang, Hsieh and Chang (2011) found that consumer knowledge was positive factor that influenced the adoption of Location-Based Services.…”
Section: Consumer Knowledge Of Mnp (Kwmnp)mentioning
confidence: 99%
“…Other studies used various established theories such as Fishbein and Ajzen's (1975), Theory of Reasoned Action (i.e., Shoham et al, 2008;Marcketti and Shelly, 2009), Ajzen's (1991) Theory of Planned Behavior (i.e., Fernades, 2013;Penz and Stottinger, 2005), and Kohlberg's (1976) Theory of Moral Reasoning (i.e., Phau et al, 2009) in order to explain the purchase of luxury brand counterfeits. Furthermore, the work of Yoo and Lee (2009) identified that consumer interest in buying counterfeit products may be affected by a number of factors such as their beliefs about the economic and hedonic benefits of counterfeit purchases, their previous purchases of originals, and their perceived future social status and self-image.…”
Section: Consumer Behaviour On Counterfeitsmentioning
confidence: 99%
“…Schreier and Prügl (2008) found that users with high level of knowledge in an innovation tend to be ahead of its market trend and expect high benefits from innovation, and would adopt new commercial products faster and more intensively than ordinary ones. Marcketti and Shelley (2009) also pointed out that consumers' knowledge of products has a significantly positive effect on their perceived ease to use. Customer's knowledge can help them identify what mobile payment can do for them, and why the products/services are important to them.…”
Section: Mobile Payment Knowledgementioning
confidence: 99%